Higher education in emergencies : best practices and benchmarking - Sengupta, Enakshi (Innovations in higher education teaching and learning, 2023)
Today's world is fraught with perils and pandemics. Education offers structure, stability, and hope for the future, supporting conflict resolution, peacebuilding efforts, and scientific research that can help prevent and mitigate both natural and manmade disasters. With these values in mind, how can universities apply their experiences from the COVID-19 pandemic to other emergency situations? How can they ensure accessibility to education under any circumstances without compromising on quality? With diverse contributions from Qatar, Kosovo, Turkey, Austria, Israel, Sweden, and the United States, Higher Education in Emergencies: Best Practices and Benchmarking challenges educators to design curriculums that focus on resilience and equip staff with the capability to navigate future scenarios, and students with the skills they need to someday solve them. Avoiding prescriptive standards and advocating for programmes that address the needs of individual campuses, chapters focus on effective methods for evaluating and assessing emergency preparedness, as well as exhibiting exemplary responses that have set a precedent for institutional adaptability moving forward. Championing tangible action and its measurable impacts, Higher Education in Emergencies: Best Practices and Benchmarking provides a critical toolkit for preparing universities for the next pandemic, earthquake, or civil conflict.